266 PROGNOSTIC VALUE OF ESOPHAGEAL PH MONITORING DURING INFANCY ON SYMPTOMS OF GASTROESOPHAGEAL REFLUX DISEASE IN CHILDREN. (1st January 2006) - Khan, S.; Puente, P.; Gremse, D.
Abstract : Gastroesophageal reflux disease (GERD) commonly causes regurgitation in infancy. The prognosis of GERD in infants is excellent as symptoms of vomiting and irritability resolve in the majority of patients by 1 year of age. Few longitudinal studies have evaluated the incidence of symptoms of GERD in children who had GERD in infancy. The aim of this study is to determine whether GERD in infancy is associated with increased symptoms of GERD in childhood. Parents of 50 children (child's age at the time of survey 8.3 ± 1.7 yr, mean ± SD, 54% male) who underwent 24-hr esophageal pH monitoring in infancy were asked about current symptoms of GERD by telephone survey. The incidence of symptoms in children who had an abnormal pH study in infancy (Johnson-DeMeester score) were compared to those with normal pH study results. We conclude that children who had GERD with abnormal esophageal pH monitoring in infancy are more likely to experience heartburn and excessive belching in childhood. Abnormal esophageal pH study results in infancy may be prognostic of an increased risk of symptoms of GERD later in childhood.